Time-based failure analysis of compressed riverbank riprap. Issue 2 (4th March 2017) - Jafarnejad, Mona; Franca, Mário J.; Pfister, Michael; Schleiss, Anton J.
ABSTRACT: Methods to design riprap-lined channels usually refer to dumped material. Large blocks placed individually by machinery are used when more stability is required. They offer additional resistance against flow erosion since space between blocks is minimized and interlocking increased. The behaviour of this protection has rarely been studied. An experimental investigation was carried out on the stability of compressed riprap as riverbank protection. Riprap was reproduced by uniform crushed limestones with three block sizes. Tests were conducted for three channel slopes under supercritical flow conditions and for constant bank slope. A time-based analysis allowed establishing relations among time to failure, friction velocity, and dimensionless bed shear stress. The results of 45 tests confirm that the rate of block erosion is significantly reduced with increase in the riprap diameter. The time to failure of the riprap protection depends strongly on the longitudinal slope and on the block sizes. An empirical prediction to estimate the riprap time to failure is shown.